2019
DOI: 10.1021/acs.biomac.9b00979
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Architecture of the Cell Wall in Living Plant Cells by Bioimaging and Enzymatic Degradation

Abstract: Plant cell walls consist mostly of crystalline cellulose fibrils embedded in a matrix of complex polysaccharides, but information on their morphological features has generally been limited to that obtained from nonliving plant specimens. Here, we characterized the primary cell wall of a living plant cell (from the tobacco BY-2 suspension culture) at nanometer resolution using high-speed atomic force microscopy and at micrometer resolution using confocal laser scanning microscopy. Our results showed aligned and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Consistent with these data, ruthenium red staining demonstrated that BY-2 cells have abundant pectin on their surface. Our findings agree with previous work that indicated that BY-2 cells produce a layer of pectin after subculture ( 59 ). Additional work is required to uncover the mechanism by which pectin mediates the adhesion of plant cells to scaffolds.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with these data, ruthenium red staining demonstrated that BY-2 cells have abundant pectin on their surface. Our findings agree with previous work that indicated that BY-2 cells produce a layer of pectin after subculture ( 59 ). Additional work is required to uncover the mechanism by which pectin mediates the adhesion of plant cells to scaffolds.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this data, ruthenium red staining demonstrated that BY-2 cells have abundant pectin on their surface. Our findings are in agreement with previous work that indicated that BY-2 cells produce a layer of pectin around four days after subculture 43 . Since the adhesion of BY-2 cells to scaffolds is reminiscent of the way cells adhere in plant tissues, our scaffolds should be suitable for plant tissue engineering.…”
Section: Cell-cell Adhesion and Electrical Signaling Between Cells Insupporting
confidence: 94%
“…e) Reproduced with permission. [ 28 ] Copyright 2020, American Chemical Society. f) Reproduced with permission.…”
Section: Recent Progress In the Fundamental Understanding Of Nanocellmentioning
confidence: 99%
“…[ 26 ] The shift in the microfibril orientation between the layers appeared to be random rather than gradual. [ 26–28 ]…”
Section: Recent Progress In the Fundamental Understanding Of Nanocellmentioning
confidence: 99%